A New Reliable Method for Evaluating Gallbladder Dynamics: The 3‐Dimensional Sonographic Examination. (6th January 2016) - Serra, Carla; Pallotti, Francesca; Bortolotti, Mauro; Caputo, Carla; Felicani, Cristina; De Giorgio, Roberto; Barbara, Giovanni; Nardi, Elena; Labate, Antonio Maria Morselli
Abstract : Objectives: The purpose of this study was to compare conventional 2‐dimensional (2D) B‐mode sonography with 3‐dimensional (3D) sonography for assessing gallbladder volume and contractility. Methods: Gallbladder volume and contractility were evaluated in 32 healthy volunteers after fasting and abstinence from smoking for 8 hours and after a standardized balanced liquid meal. The gallbladder was evaluated with 2D sonography (with the use of the ellipsoid method) and with 3D sonography using a volumetric matrix probe. Both measurements were made by an operator who was skilled in sonography and an unskilled operator. The group of volunteers was subdivided into 2 subgroups including 16 participants, which represented the "2 moments" of acquisition by the techniques, particularly for the unskilled operator. Results: The postprandial volumes obtained with 3D sonography were significantly lower in comparison to the volumes obtained with 2D sonography ( P = .013), and there was a significant difference between the measurements made by the skilled and unskilled operators only for 2D sonography ( P < .001), whereas between the 2 moments of acquisition by the 3D technique, there was no significant difference. The reproducibility of the technique for evaluation of gallbladder volumes was higher for 3D sonography than 2D sonography, particularly for the postprandial evaluation. Conclusions: The new 3D sonographic method using a volumetric matrix probe is a simple, reliable, and more reproducible technique than conventional 2D sonography, even if performed by an unskilled operator, and it allows a reliable stimulation test for a gallbladder dynamic study.